2022
DOI: 10.1111/aphw.12347
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in life and personal growth: The unique and joint contribution of physical activity and basic psychological needs

Abstract: This study examined if physical activity (PA) and self‐determination theory's basic psychological needs directly or interactively predict older adults' eudaimonic well‐being. Participants aged ≥55 years completed five online surveys. At baseline (T1), participants (N = 430) reported on autonomy, competence, and relatedness experienced during PA. PA was assessed prospectively using the Physical Activity Scale for Elderly (recall period = 7 days) for four consecutive weeks (T2, T3, T4, and T5); weekly PA scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Findings from prospective studies on the antecedents of purpose align with the notion that one’s capacity or motivation to develop and maintain a sense of purpose depends somewhat on previous emotional well-being (Hedberg et al, 2011) and fulfilment of psychological needs (Teas et al, 2022). In one study, depression in old adulthood was associated with larger declines in sense of purpose after five years (Hedberg et al, 2010), and another study found that higher scores on depression and anxiety and lower scores on positive affect predicted lower sense of purpose eight years later (Chen et al, 2020).…”
Section: Introductionsupporting
confidence: 59%
“…Findings from prospective studies on the antecedents of purpose align with the notion that one’s capacity or motivation to develop and maintain a sense of purpose depends somewhat on previous emotional well-being (Hedberg et al, 2011) and fulfilment of psychological needs (Teas et al, 2022). In one study, depression in old adulthood was associated with larger declines in sense of purpose after five years (Hedberg et al, 2010), and another study found that higher scores on depression and anxiety and lower scores on positive affect predicted lower sense of purpose eight years later (Chen et al, 2020).…”
Section: Introductionsupporting
confidence: 59%
“…Interestingly, these two main individual predictors of personal growth display different levels of the nature of personal growth triggered by divorce since purpose in life measures the extent to which individuals explicitly orientate (i.e., structure) their initiatives of personal growth and their efforts to understand, provide significance, meaning and directedness to their lives, while the motivation for personality growth goals reveals whether the content of goals reflects intentional efforts to pursue personal growth (Bauer et al, 2019;Bauer & McAdams, 2004). The relationship between purpose in life and personal growth was expected since previous findings have shown a moderate positive correlation between these two scales of the PWBS (Ryff & Keyes, 1995;Teas et al, 2022). The predictive value of purpose of life in personal growth should be cautiously interpreted as both constructs were measured using the PWBS.…”
Section: Discussionmentioning
confidence: 99%
“…We considered purpose in life, a growth-related dimension of psychological well-being (Staudinger & Kessler, 2009); divorce-related selfexpansion, which describes the evaluation of new or augmented gains in self-improvement as a consequence of the divorce adversity (Hughes et al, 2020); psychological mindedness, defined as the interest in and ability for understanding one's psychological states and processes (Appelbaum, 1973;Nyklí cek & Denollet, 2009); and motivational orientation for personality growth goals, which highlights an aspiration to think complexly and coherently in the exploration and gaining of new (self-transcending) perspectives on one's psychosocial life (Bauer et al, 2015(Bauer et al, , 2019. Previous research has documented associations between these four personality indicators and personality growth criteria (Hughes et al, 2020;Teas et al, 2022;Wink & Staudinger, 2016).…”
Section: Key Practitioner Messagementioning
confidence: 99%
“…To support all three basic human psychological needs is important for engagement in physical activity. In a study by Teas et al ( 26 ), simply to engage in physical activity was not enough to improve a sense of wellbeing among older adults. The activities also needed to be supportive of all of the psychological needs ( 26 ).…”
Section: Methodsmentioning
confidence: 97%
“…In a study by Teas et al ( 26 ), simply to engage in physical activity was not enough to improve a sense of wellbeing among older adults. The activities also needed to be supportive of all of the psychological needs ( 26 ). A meta-analysis confirmed the importance of incorporating elements of all three needs to support physical activity behavior ( 27 ).…”
Section: Methodsmentioning
confidence: 97%